The The Effectiveness of Physics Practicum Simulations for First-Year University Students: Efektivitas Simulasi Praktikum Fisika pada Mahasiswa Tahun Pertama - Dwila Sempi Yusiani; Meylia Vivi Putri; Rafi Dio (Jurnal Teknik Ibnu Sina (JT-IBSI), 2025)
The lack of laboratory facilities in the Industrial Engineering program poses challenges for conducting physics practicums. Practicum is an essential component of learning as it enhances conceptual understanding and student motivation. This study aims to determine the effectiveness of using PhET Simulation as a virtual laboratory tool to support student understanding of Hooke’s Law. A quantitative method was used with a one-group pretest-posttest design involving 31 first-year students. Data were collected through pretest and posttest assessments, and analyzed using descriptive statistics and N-Gain calculation. The results show an increase in the average score from pretest to posttest, with an N-Gain score of 0.36, categorized as moderate. These findings suggest that PhET Simulation is fairly effective in enhancing physics learning through visual and interactive approaches, especially in limited laboratory conditions. This study contributes to the development of technology-based learning media that can be implemented flexibly in higher education.